Nurses' Finnegan Scoring of Newborns with Neonatal Abstinence Syndrome Not Affected by Time or Day of the Week - Kushnir, Alla; Bleznak, Jennifer L.; Saslow, Judy G.; Stahl, Gary (American Journal of Perinatology, 2020)
Objective Newborns exposed to drugs in utero are at risk of developing neonatal abstinence syndrome (NAS), characterized by behavioral changes and physiologic instability. Finnegan scoring tool quantifies severity of symptoms and guides treatment. This article evaluates whether time of day and the number of shift hours affects modified Finnegan scores, and the subjective component of these scores.Study Design Institutional review board-approved, retrospective chart review of newborns admitted to neonatal intensive care or transitional nursery from 2011 to 2014. Inclusion criteria: > 35 weeks' gestation, known maternal substance use, positive maternal or newborn urine, or meconium drug screen, NAS treatment.Results A total of 101 charts were evaluated. Mean treatment duration was 31.8 days (standard deviation ±18.3). There was no significant relationship between observer shift hour and high scores (> 8) (p = 0.83). Highest scores occurred in the afternoon, decreased at night (p = 0.03), and throughout admission (p < 0.0001). Weekend and weekday scores were similar (p = 0.4). The objective component of the scores remained similar throughout the day (p = 0.91) and week (p = 0.52).Conclusion Finnegan scores given by nurses were not influenced by shift hour. Time of day did not influence overall high scores or the proportion of objective to total Finnegan score. Inter-rater reliability was maintained regardless of time of day or day of the week.
Keywords: neonatal abstinence syndrome; withdrawal; Finnegan scoring; nursing fatigue